To the Question of the Civil Nature of Legal Succession - E. A. Sautkina (Сибирское юридическое обозрение, 2019)
The article is devoted to the analysis of the essence of legal succession from the standpoint of the science of civil law. The Author proposes to consider this category to be a legal relationship of a general type. Approaches to the definition of the content of the category «legal relationship» are considered, and the differences between general and specific legal relations are analyzed. The article reveals the elements of legal relationship of legal succession of general type: subjects, object, content. The question of the object of legal relations of succession is considered in the context of a more general question of the object of civil law, civil relations and civil turnover. It is established that the content of the legal relationship of succession of the general type has a certain specificity due to the difference in the legal nature of General and specific legal relations. The situations in which on the basis of legal relations of a general type there are specific legal relations are presented. The features of the protection of the ability for legal succession are analyzed.